A Penerapan Metode Statistical Quality Control Pada Pengendalian Kualitas Gula - Muchammad 'Ahdan Sahali Ahdan; Dwi Sukma Donoriyanto Dwi Sukma Donoriyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
PT. X is part of ID FOOD which focuses on the sugar cane agro-industry sector. SHS sugar is the main product. To ensure production meets consumer standards and expectations, it is necessary to implement quality control during the production process. This involves quality control, improvement and improvement of systems so that the products produced are superior and competitive. In writing this article, the author is interested in exploring the problem of product defects and deviations in the production process, including defective products, as well as efforts to improve and improve product quality. The problem solving method used is the new seven tools, with an emphasis on affinity diagrams, linkage diagrams, tree diagrams, and PDPC. The results of data analysis suggest solutions, including implementing appropriate SOPs at each stage of production, routine maintenance on equipment every milling season, and additional training for operators or workers to increase productivity and product quality